2012
DOI: 10.3325/cmj.2012.53.254
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities, health damaging behavior, and self-perceived health in Serbia: a cross-sectional study

Abstract: AimTo analyze the association of socioeconomic factors with self-perceived health in Serbia and examine whether this association can be partly explained by health behavior variables.MethodsWe used data from the 2007 Living Standards Measurement Study for Serbia. A representative sample of 13 831 persons aged ≥20 years was interviewed. The associations between demographic factors (age, sex, marital status, and type of settlement), socioeconomic factors (education, employment status, and household consumption te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
6
9
0
Order By: Relevance
“…Results revealed that all four analysed socioeconomic factors were significantly associated with poor self-perceived health, not only in a univariate model, but also in a multivariable model controlled for demographic and lifestyle factors, suggesting that their association with poor self-perceived health is not mediated by demographic and lifestyle factors included in this analysis. This conclusion is confirmed by results of studies in other populations (Kraja, Kraja, Cakerri, & Burazeri, 2016;Janković, Janević, & Von dem Knesebeck, 2012). Similar findings were in line with some studies suggesting that self-perceived social status was related to self-rated health and irrespective of sex, self-perceived social status was related to self-rated health, depression, and long--standing illness or disability over and above education, occupational status, wealth, age, and marital status (Franzini & Fernandez-Esquer, 2006;Hu, Adler, Goldman, Weinstein, & Seeman, 2005;Ostrove, Feldman, & Adler, 1999;Singh-Manoux, Marmot, & Adler, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…Results revealed that all four analysed socioeconomic factors were significantly associated with poor self-perceived health, not only in a univariate model, but also in a multivariable model controlled for demographic and lifestyle factors, suggesting that their association with poor self-perceived health is not mediated by demographic and lifestyle factors included in this analysis. This conclusion is confirmed by results of studies in other populations (Kraja, Kraja, Cakerri, & Burazeri, 2016;Janković, Janević, & Von dem Knesebeck, 2012). Similar findings were in line with some studies suggesting that self-perceived social status was related to self-rated health and irrespective of sex, self-perceived social status was related to self-rated health, depression, and long--standing illness or disability over and above education, occupational status, wealth, age, and marital status (Franzini & Fernandez-Esquer, 2006;Hu, Adler, Goldman, Weinstein, & Seeman, 2005;Ostrove, Feldman, & Adler, 1999;Singh-Manoux, Marmot, & Adler, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study correlate to results of various different studies which point to the fact that the level of education is in a proportional relationship with the selfassessment of health 13,14 and that it is possible that the inequality in healthcare is a consequence of the perceived fact that the people with higher education have more skills for solving everyday challenges which could have a negative influence on the health of an individual 15 .…”
Section: Discussionsupporting
confidence: 84%
“…[9] In addition, medical studies have found that stress increases both eating and smoking. [31][32][33][34] Moreover, job loss affects health behavior through an income effect.…”
Section: Discussionmentioning
confidence: 99%